STUDENTS DIFFICULTIES IN LEARNING WRITING ABILITY AT STAIN BENGKALIS - Rini Anggraini; Ranisa, Ranisa; Ahmad Jailani (Cahaya Ilmu Bangsa Institute, 2024)
Writing is usually one of the things that must be mastered by everyone. Especially students, many of them face difficulties in writing. This study explores the challenges faced by students in acquiring writing comprehension skills. It delves into various factors contributing to these difficulties, including language barriers, lack of writing practice, and ineffective teaching methods. The research employs a mixed-methods approach, combining surveys and qualitative analyses to gather comprehensive insights. Findings reveal a need for targeted interventions, such as tailored instructional strategies and increased exposure to diverse writing genres, to enhance students' writing comprehension abilities. The study contributes valuable information for educators, curriculum developers, and policymakers aiming to improve writing education outcomes. The latter suggests that some of the difficulties students face in learning to write are a lack of confidence that prevents them from writing, limited vocabulary, making it difficult for them to compose the words they want to write and often fear that others will criticize their writing. This research not only focuses on the complex challenges that hinder students' writing comprehension, but also provides a foundation for developing writing proficiency.